SISTEM INFORMASI GEOGRAFIS POTENSI GENANGAN BANJIR DI DEMAK - Eka Setyabudi; Bambang Agus Herlambang, Ahmad Khoerul Anam (CV. Adiba Aisha Amira, 2024)
Demak Regency is one of the districts in the province of Central Java, Indonesia. The capital city is Demak Kota District, this district borders the Java Sea to the west, Jepara Regency to the north, Kudus Regency to the east, Grobogan Regency to the southeast, and Semarang City and Semarang Regency to the west. Demak Regency is one of the areas in north coast of Java. As a coastal area, apart from having great potential, the coast in Demak Regency is also an area prone to land subsidence and tidal flooding. This research aims to analyze the potential for flood inundation in Demak Regency using a Geographic Information System (GIS) approach. Spatial data in the form of land elevation, rainfall and land use are collected and analyzed using the latest GIS software. The results of the analysis show the identification of areas that have the potential to experience flood inundation, with topography and land use factors playing a crucial role in determining the level of risk. This research contributes to understanding the potential for flood inundation in Demak Regency and can be the basis for future disaster risk mitigation and management policies.